1991
DOI: 10.1093/oxfordjournals.humrep.a137439
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal secretory function in men with asthenoteratozoospermia

Abstract: Epididymal function was evaluated in normozoospermic men and men with asthenoteratozoospermia using alpha-glucosidase as a secretory parameter. No difference was observed in the total quantity of the enzyme secreted into the ejaculate in spite of major differences between the two groups in the proportion of spermatozoa exhibiting progressive motility and normal morphology. In general, the secretion of alpha-glucosidase was positively correlated with the sperm concentration in the normozoospermic group, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(1990) that α‐glucosidase in semen is a marker of epididymal function and specifically of the development of motility. Purvis et al . (1991) concluded that, if α‐glucosidase is a reliable parameter of human epididymal secretory function, variation in the secretory function of the epididymis cannot explain the poor sperm quality observed in asthenoteratozoospermic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…(1990) that α‐glucosidase in semen is a marker of epididymal function and specifically of the development of motility. Purvis et al . (1991) concluded that, if α‐glucosidase is a reliable parameter of human epididymal secretory function, variation in the secretory function of the epididymis cannot explain the poor sperm quality observed in asthenoteratozoospermic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the decrease in sperm quality in the presence of a normal sperm count can Paraplegia 31 (1993) [3][4][5][6][7][8][9][10][11][12] be explained by senile degeneration of the cells due to prolonged storage in the cauda epididymis and vas deferens. Furthermore, ejaculations induced at weekly intervals did not appear to be sufficient to empty the stores of aging sperm, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…Additional aliquots (50 }.tl) of the samples were subjected to vital staining using eosin Paraplegia 31 (1993) [3][4][5][6][7][8][9][10][11][12] Y and nigrosin as described by Blom6 as well as Harris' haematoxylin for the assess ment of morphology. Microcephalic, macro cephalic, bicephalic, bicaudal spermatozoa or cells possessing a coiled tail or a de formed or abnormally small acrosome were all classified as abnormal.…”
Section: Sperm Analysismentioning
confidence: 99%